The Melbourne Consensus Statement on the early detection of prostate cancer. (February 2014) - Murphy, Declan G.; Ahlering, Thomas; Catalona, William J.; Crowe, Helen; Crowe, Jane; Clarke, Noel; Cooperberg, Matthew; Gillatt, David; Gleave, Martin; Loeb, Stacy; Roobol, Monique; Sartor, Oliver; et al.
Abstract : Various conflicting guidelines and recommendations about prostate cancer screening and early detection have left both clinicians and their patients quite confused. At the Prostate Cancer World Congress held in Melbourne in August 2013, a multidisciplinary group of the world's leading experts in this area gathered together and generated this set of consensus statements to bring some clarity to this confusion. The five consensus statements provide clear guidance for clinicians counselling their patients about the early detection of prostate cancer.